Social Media Marketing as a Catalyst for Brand Awareness and Purchase Decisions: Evidence from New Balance Shoe Consumers - Septiyani, Sati (APPS Publications, 2024)
The purpose of this study is to determine the influence of Social Media Marketing and Brand Awareness on the decision to purchase New Balance brand shoes, and this study focuses on New Balance shoe consumers. A quantitative methodology is employed in this study, utilizing a cluster sampling technique to gather data from a minimum of 96 respondents through questionnaires distributed via Google Forms, with the analysis conducted using Smart PLS SEM software to explore the relationships between service quality, price, perceived value, and customer satisfaction. Social media marketing significantly influences both purchasing decisions and brand awareness for New Balance shoe products, confirming the hypotheses that higher engagement and effectiveness in social media marketing lead to increased consumer purchasing behavior and brand recognition. Additionally, brand awareness itself has a substantial impact on purchase decisions, suggesting that as consumers become more aware of and familiar with the brand, they are more likely to choose it when making purchasing decisions, thereby highlighting the interconnected roles of social media marketing and brand awareness in driving consumer behavior. The novelty of this research lies in its comprehensive examination of the interconnected relationships between social media marketing, brand awareness, and purchasing decisions specifically within the context of New Balance shoes. While previous studies have explored these variables in isolation, this research uniquely integrates them to demonstrate how effective social media marketing not only enhances brand awareness but also directly influences consumer purchasing behavior.